2022
DOI: 10.2174/0929866529666220217124152
|View full text |Cite
|
Sign up to set email alerts
|

The Amyloid Precursor Protein Plays Differential Roles in the UVA Resistance and Proliferation of Human Retinal Pigment Epithelial Cells

Abstract: Background: Age-related macular degeneration (AMD) can be characterised by degeneration of retinal pigment epithelial (RPE) cells and the accumulation, in retinal drusen deposits, of amyloid beta-peptides proteolytically derived, by secretases, from the amyloid precursor protein (APP). Ultraviolet (UV) light exposure is a risk factor for the development of AMD. Objectives: In the current study, we investigated whether APP and/or its proteolysis are linked to the UVA resistance or proliferation of ARPE-19 hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Oxidative stress within the retina is exacerbated by chronic UVA exposure affecting all retinal structures. Moreover, blue light exposure is known to induce oxidative stress within the retinal pigment epithelium (RPE) layer [7,8]. The cumulative oxidative stress from UV and blue light, which is further potentiated by cigarette smoke and the aging process, elevates the reactive oxygen species (ROS) levels produced by the RPE.…”
Section: Pathophysiology and Risk Factors Of Amd 21 Oxidative Stress ...mentioning
confidence: 99%
“…Oxidative stress within the retina is exacerbated by chronic UVA exposure affecting all retinal structures. Moreover, blue light exposure is known to induce oxidative stress within the retinal pigment epithelium (RPE) layer [7,8]. The cumulative oxidative stress from UV and blue light, which is further potentiated by cigarette smoke and the aging process, elevates the reactive oxygen species (ROS) levels produced by the RPE.…”
Section: Pathophysiology and Risk Factors Of Amd 21 Oxidative Stress ...mentioning
confidence: 99%
“…It is well-documented that the astrocytes affected by AD express high levels of APP, βsecretase, and γ-secretase, the three main components required for amyloid production [29]. Proteolysis of APP by α-secretase and β-secretase leads to the secretion of sAPPα and sAPPβ, respectively [36]. The secreted sAPPα or sAPPβ have C-terminal fragments which can be cleaved by γ-secretase extracellularly to release the peptides Aβ42 and Aβ40 [36].…”
Section: Protein Aggregation In Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Proteolysis of APP by α-secretase and β-secretase leads to the secretion of sAPPα and sAPPβ, respectively [36]. The secreted sAPPα or sAPPβ have C-terminal fragments which can be cleaved by γ-secretase extracellularly to release the peptides Aβ42 and Aβ40 [36]. Zhao et al studied the effect of cytokines on the production of amyloids in the astrocytes of the brain in AD-affected patients.…”
Section: Protein Aggregation In Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Then amyloid beta can activate the alternative complement pathway. It has been claimed that these effects can be mitigated by using blue light-filtering devices [19]. Nevertheless, there are conflicting results in the scientific literature regarding its use to prevent the onset of AMD in humans, and more studies are needed to demonstrate with certainty the benefit beyond what was observed in vitro [20].…”
Section: Oxidative Stressmentioning
confidence: 99%